The Dynamics of Portfolio Management Contracts - Heinkel, Robert; Stoughton, Neal M. (Review of Financial Studies, 1994)
[We consider the multiperiod relationship between a client and a portfolio manager and the resulting problem of motivating a manager of unknown ability to acquire valuable information. We explore the contractual forms and the optimal retention policy of the client and find that the optimal initial set of contracts features a smaller performance-based fee component paid to the manager than in a first-best contract, and the contract choice elicits only partial information about the manager. As a result, ex post performance measurement is critical to future recontracting. In general, managers are retained only if the returns on their portfolio exceed the benchmark by an appropriate amount.]